The Fairness of Pricing Tactics for Hotels: Perceptions of Romanian Customers - Claudia-Elena Țuclea; Diana Maria Vrânceanu; Carmen-Eugenia Năstase (Amfiteatru Economic)
This study focuses on analysing the perceptions of pricing tactics the hotels from Romania use, and also on the degree of influence these perceptions have on buying intentions. Given the importance of perceived fairness, it is essential to understand the major factors that influence customers’ perception of the fairness of prices set by revenue management methods. A nationwide survey was conducted to identify the perception of fairness of the price setting methods, the perception of price fairness in relation to certain factors of influence, the perceived fairness of different pricing tactics, and the evaluation of price fairness for the latest experience in a hotel and the influence on the purchasing intentions. Structural equation modelling was used to assess the influence of distributive and procedural fairness on the perceived value and the buying intentions. The resulting model essentially shows that tourists who perceive a price as fair are inclined to consider the method used to set that price as correct. The main findings regarding revenue management-type approaches emphasize that the price setting method oriented on competition is considered the fairest method for setting prices. Most survey participants believe that the most frequent situation of unfair price is found in accommodation services. Among the unfair pricing tactics are, on the one hand the difference of prices based on the nationality of the customers (higher prices for tourists from abroad) and, on the other hand, the 9-ending prices. Offering lower prices for longer periods and for larger groups represents the fairest pricing tactics that hotels can use. The manners in which Romanian customers use to rate price fairness for hotel services mainly relies on the comparison of the current price to a previous one, and on their own belief of what fair price should be. The managerial implication of this study is linked to the setting prices decisions in order to be perceived as fair prices/tariffs